El material didáctico y su influencia en el rendimiento académico de los estudiantes del primero y segundo grado de educación general básica de la escuela mixta José Ingenieros nº 1, del cantón y provincia de Loja. Periodo 2012 - 2013 - Sánchez Cueva, Mónica Karina (2014)
The presentin vestigation called "THE TEACHING MATERIALSAND THEIR INFLUENCE ONTHEACADEMIC PERFORMANCEOF STUDENTSOF THEFIRST AND SECOND GRADE GENERAL EDUCATIONSCHOOLJOINTBASEENGINEERJOSEPHN°1, CANTONANDTHEPERIOD2012-2013Lojaprovince" As a general goal, characterize the influence of the teaching materials in improving the academic performance of students in the Joint Engineer Joseph School No. 1. Scientific methods used descriptive method. deductive - Inductive Method. Hypothetical - deductive. The techniques used were: the survey used to teachers and students of the institution to recognize on teaching materials and academic achievement of meaningful learning of the children in the institution in which four teachers 35 first graders and 35 students participating second level of Engineer José Mixed School no.1. As a result of the implementation of the survey a high percentage regarding the use of teaching materials with good meaningful learning for them it is recommended it was found that teachers who have obligations to ensure their children give their necessary support to achieve obtain a progress on meaningful learning Pursuant to this premise the study on the influence of the teaching materials in academic performance is done , trying to help and encourage the possibility of improving the academic achievement levels of students.